2016
DOI: 10.2967/jnumed.116.174391
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Imaging for Classic Fever of Unknown Origin: Meta-Analysis

Abstract: Several studies have assessed nuclear imaging tests for localizing the source of fever in patients with classic fever of unknown origin (FUO); however, the role of these tests in clinical practice remains unclear. We systematically reviewed the test performance, diagnostic yield, and management decision impact of nuclear imaging tests in patients with classic FUO. Methods: We searched PubMed, Scopus, and other databases through October 31, 2015, to identify studies reporting on the diagnostic accuracy or impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 42 publications
(51 reference statements)
2
53
2
2
Order By: Relevance
“…Fluorodeoxyglucose‐positron emission tomography combined with X‐ray computed tomography (FDG‐PET/CT) imaging has been used for many years as an effective method to stage and restage malignancies . Several studies have demonstrated high sensitivity of FDG‐PET/CT for diagnosis of infection of prosthetic devices, osteomyelitis and determining the aetiology of pyrexia of unknown origin (PUO) . Small studies have also demonstrated high clinical impact of FDG‐PET/CT in patients with neutropenic fever (NF) of unclear cause, with benefits of de‐escalating or rationalising antimicrobials, of directing further investigation such as bronchoscopy or tissue sampling and establishing an aetiological diagnosis of NF .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorodeoxyglucose‐positron emission tomography combined with X‐ray computed tomography (FDG‐PET/CT) imaging has been used for many years as an effective method to stage and restage malignancies . Several studies have demonstrated high sensitivity of FDG‐PET/CT for diagnosis of infection of prosthetic devices, osteomyelitis and determining the aetiology of pyrexia of unknown origin (PUO) . Small studies have also demonstrated high clinical impact of FDG‐PET/CT in patients with neutropenic fever (NF) of unclear cause, with benefits of de‐escalating or rationalising antimicrobials, of directing further investigation such as bronchoscopy or tissue sampling and establishing an aetiological diagnosis of NF .…”
Section: Introductionmentioning
confidence: 99%
“…1 Several studies have demonstrated high sensitivity of FDG-PET/ CT for diagnosis of infection of prosthetic devices, osteomyelitis and determining the aetiology of pyrexia of unknown origin (PUO). [2][3][4] Small studies have also demonstrated high clinical impact of FDG-PET/CT in patients with neutropenic fever (NF) of unclear cause, with benefits of de-escalating or rationalising antimicrobials, of directing further investigation such as bronchoscopy or tissue sampling and establishing an aetiological diagnosis of NF. 5,6 There is emerging evidence that FDG-PET/CT is more sensitive for invasive fungal infection (IFI), its dissemination and response to therapy compared to traditional computed tomography (CT).…”
Section: Introductionmentioning
confidence: 99%
“…This nuclear imaging test has shown its utility in patients with FUO, along with reasonable performance [7].…”
Section: Discussionmentioning
confidence: 99%
“…Ein weiterer Vorteil der FDG-PET ist die sensitive Detektion von malignen Erkrankungen, da diese in bis zu 25 % für die Entstehung von Fieber unklarer Genese verantwortlich sind. Auch Autoimmunerkrankungen werden durch die PET detektiert, wodurch die FDG-PET prädestiniert ist, die drei häufigsten Ursachen von Fieber unklarer Genese zu diagnostizieren, ein klarer Vorteil auch gegenüber der Leukozyten-Szintigrafie [24,48].…”
Section: Fieber Unklarer Geneseunclassified